Manfaat yang dirasakan dari sistem informasi kesehatan elektronik E-SISMAL untuk pencegahan dan surveillans malaria di Provinsi Papua Barat - Sumarandak, Switly; I. Inan, Dedi; Juita, Ratna; Indra, Muhammad (Cassowary, 2025)
ABSTRACT: E-SISMAL as a Health Information System (HIS). s crucial for preventing and surveilling malaria in Indonesia by enhancing data quality and reporting. Accurate and efficient data collection is vital for combating this disease. Despite E-SISMAL's mandatory adoption across all Indonesian provinces. challenges persist This study investigates the perceived benefits of E-SISMAL and factors influencing its successful adoption, utilizing the Technology Adoption Model (TAM) and DeLone & McLean IS Success Model. Key factors include user training. system accessibility and real-time validation. A quantitative approach involved 108 healthcare professionals in West Papua Province. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings ineffidicate E-SISMAL improves data accuracy and reporting efficiency. aligning with study objectives. However. significant technical challenges and resistance to change remain obstacles. The study highlights the need to address digital skill gaps among healthcare workers for optimal system use. Incorporating user-centered design and local context can improve usability and acceptance. Enhanced user training and system integration can further optimize E-SISMAL's efficiency. while fostering digital adaptation supports data-driven decision-making. Ultimately this study offers actionable insights for system developers and policymakers aiming to improve health information systems in remote and under-resourced regions. These findings confirm the crucial role of identified factors in E-SISMAL's successful implementation. providing a basis for strategies to enhance the system within healthcare practices